Insights into Soluble Toll-Like Receptor 2 as a Downregulator of Virally Induced Inflammation - Henrick, Bethany M.; Yao, Xiao-Dan; Taha, Ameer Y.; German, J. Bruce; Rosenthal, Kenneth Lee (Frontiers in Immunology, 2016)
The ability to distinguish pathogens from self-antigens is one of the most important functions of the immune system. However, this simple self versus non-self assignment belies the complexity of the immune response to threats. Immune responses vary widely and appropriately according to a spectrum of threats and only recently have the mechanisms for controlling this highly textured process emerged. A primary mechanism by which this controlled decision-making process is achieved is via Toll-like receptor (TLR) signaling, and the subsequent activation of the immune response coincident with the presence of pathogenic organisms or antigens, including lipid mediators. While immune activation is important, the appropriate regulation of such responses is also critical. Recent findings indicate a parallel pathway by which responses to both viral and bacterial infections is controlled via the secretion of soluble TLR2 (sTLR2). sTLR2 is able to bind a wide range of pathogen-associated molecular patterns (PAMPs) and danger-associated molecular patterns (DAMPs). sTLR2 has been detected in many bodily fluids and is thus ubiquitous in sites of pathogen appearance. Interestingly, growing evidence suggests that sTLR2 functions to sequester PAMPs and DAMPs to avoid immune activation via detection of cellular-expressed TLRs. This immune regulatory function would serve to reduce the expression of the molecules required for cellular entry, and the recruitment of target cells following infection with bacteria and viruses. This review provides an overview of sTLR2 and the research regarding the mechanisms of its immune regulatory properties. Furthermore, the role of this molecule in regulating immune activation in the context of HIV infection via sTLR2 in breast milk provides actionable insights into therapeutic targets across a variety of infectious and inflammatory states.